2016
DOI: 10.3109/13880209.2015.1107748
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative and antioxidant effects of myrtle berry seed (Myrtus communis) extract during reflux-induced esophagitis in rats

Abstract: Context Myrtle, Myrtus communis L. (Myrtaceae), is a medicinal plant well known for its richness in phenolic compounds and its beneficial effects for the treatment of gastrointestinal disorders. Objective In the present work, the protective effect of the myrtle berry seed aqueous extract (MBSAE) against esophageal reflux (ER)-induced damage in esophagus mucosa as well as the mechanisms implicated was determined. Materials and methods In this respect, adult male Wistar rats were used and divided into seven grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…In modern medicine, RE is a multifactorial disorder and esophageal pathology most frequently occurring in gastrointestinal disease and has a significant impact on the quality of life and medical costs [21,22]. e main pathogenesis of RE is complex and diverse, including esophageal mucosal irritability, decreased esophageal capacity, decreased esophageal sphincter function, and gastric motility disorders [23].…”
Section: Resultsmentioning
confidence: 99%
“…In modern medicine, RE is a multifactorial disorder and esophageal pathology most frequently occurring in gastrointestinal disease and has a significant impact on the quality of life and medical costs [21,22]. e main pathogenesis of RE is complex and diverse, including esophageal mucosal irritability, decreased esophageal capacity, decreased esophageal sphincter function, and gastric motility disorders [23].…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies have shown that esophagitis induced by gastroesophageal reflux is mediated by reactive oxygen species (ROS) [13][14][15][16]. The role of ROS has been extensively studied in gastric and esophageal mucosal lesions induced by the administration of NSAIDs such as aspirin [17] or ethanol [18] as well as by ischemia [6].…”
Section: Involvement Of Oxidative Stress In the Pathophysiology Of Rementioning
confidence: 99%
“…According to recent studies on animal models [14,24,25], it has been shown that gastroesophageal reflux promotes the production of ROS, which leads to lesions of the esophageal mucosa. Reactive oxygen species appear to be a major cause of esophageal lesion during GER.…”
Section: Free Oxygen Derivatives and Caustic Injuries Of Esophagus Dumentioning
confidence: 99%
“…Since the publication of this trial, there has been one rat study that found beneficial effects of myrtle berry seed aqueous extract against oesophageal reflux‐induced damage of the oesophagus . Overall, the evidence that myrtle extracts are efficacious against GORD remains sketchy.…”
Section: Commentarymentioning
confidence: 99%